BioFACTS: biomarkers of rhabdomyolysis in the diagnosis of acute compartment syndrome – protocol for a prospective multinational, multicentre study involving patients with tibial fractures - Johan Lyth; Jörg Schilcher; Andrew Schmidt; Lasse Rämö; Björn Alkner; Abraham Nilsson; Thomas Ibounig; Ferdinand von Walden; Lotta Fornander (BMJ Open, 2022)
Introduction The ischaemic pain of acute compartment syndrome (ACS) can be difficult to discriminate from the pain linked to an associated fracture. Lacking objective measures, the decision to perform fasciotomy is based on clinical findings and performed at a low level of suspicion. Biomarkers of muscle cell damage may help to identify and monitor patients at risk, similar to current routines for patients with acute myocardial infarction. This study will test the hypothesis that biomarkers of muscle cell damage can predict ACS in patients with tibial fractures.Methods and analysis Patients aged 15–65 years who have suffered a tibial fracture will be included. Plasma (P)-myoglobin and P-creatine phosphokinase will be analysed at 6-hourly intervals after admission to the hospital (for 48 hours) and—if applicable—after surgical fixation or fasciotomy (for 24 hours). In addition, if ACS is suspected at any other point in time, blood samples will be collected at 6-hourly intervals. An independent expert panel will assess the study data and will classify those patients who had undergone fasciotomy into those with ACS and those without ACS. All primary comparisons will be performed between fracture patients with and without ACS. The area under the receiver operator characteristics curves will be used to identify the success of the biomarkers in discriminating between fracture patients who develop ACS and those who do not. Logistic regression analyses will be used to assess the discriminative abilities of the biomarkers to predict ACS corrected for prespecified covariates.Ethics and dissemination The study has been approved by the Regional Ethical Review Boards in Linköping (2017/514-31) and Helsinki/Uusimaa (HUS/2500/2000). The BioFACTS study will be reported in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology recommendations.Trial registration number NCT04674592.